Optimasi Konsentrasi VCO Terhadap Stabilitas Fisik Facewash dan Uji Antibakteri Ekstrak Daun Kelapa Sawit (Eleais Guineensis Jacq.) pada Bakteri Penyebab Jerawat: Optimization of VCO Concentration on Physical Stability of Facewash and Antibacterial Test of Oil Palm Leaf Extract (Eleais Guineensis Jacq.) on Acne-causing Bacteria - Selin Cenora Aritonang; Wisnu Cahyo Prabowo; Angga Cipta Narsa; Riski Sulistiarini; Helmi Helmi (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Palm oil leaves (Elaeis guineensis Jacq.) is a waste from oil palm plantations which contain flavonoid, steroid, and alkaloid compounds that function as an antibacterial that causes acne. The purpose of this research was to identify determine the concentration of ethanolic extract of oil palm leaves which is effective in inhibiting acne-causing bacteria and to determine the best formulation that can produce a facewash base that fulfill the requirements for stability of the preparation according to SNI. Antibacterial test of oil palm leaf extract was using the pitting method against acne-causing bacteria. The results of the antibacterial test showed that the extract concentration of 75% had antibacterial activity against the growth of acne-causing bacteria. The facewash base was obtained by varying the VCO with concentrations of 17.5%, 20%, and 22.5%. The results of the evaluation of the facewash base formula for 28 days, namely F2 (20%) produced good characteristics and stability, namely a distinctive aroma, cream color, semi-solid form, pH 6,25 – 6,37, viscosity 0,904 -2,700 Pa.s, high foam stability. 89% - 100% and good homogeneity. The three base formulas have fulfill requirements for facewash according to SNI.